Hubungan antara Intensitas Penggunaan Aplikasi Streaming Berbayar dan Tingkat Kekayaan Konten (content richness) yang Ditawarkan dengan Loyalitas Konsumsi Aplikasi Streaming Berbayar GoPlay - Hutauruk, Bagas; Pudjo Santosa, Hedi; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
GoPlay, which is a streaming application from Gojek, has several exclusive series, the majority of which are Indonesian films or series, which are unique and different from their competitors. GoPlay has several livestream content which is also filled by Indonesian content creators. In the midst of the high streaming flow that occurs in Indonesia with 3 billion hours per month, but in fact GoPlay is only ranked 10th out of the 10 most used streaming applications list, as of January 2021 the GoPlay application on the AppStore only ranked 86th in the Top Chart Entertainment App Store. This study aims to determine the correlation among intensity of paid streaming application usage and the level of content richness offered with the consumption loyalty of GoPlay paid streaming application. Uses and Gratification theory is used in this study with a sampling technique in the form of non-probability sampling. The sample used is 50 respondents with female and male characteristics, aged 20-34 years, active and passive users of the GoPlay paid streaming application. In testing this study using the Multiple Correlation test. The results of the study prove that there is a relationship between the intensity of the use of paid streaming applications and the level of content richness offered with the loyalty of consumption of the paid streaming application GoPlay has a significance value of 0.000 which means it is very significant with a correlation coefficient value of 0.585, which is a strong relationship and direction positive relationship occurs between variables.